Clinical phenotype, NOD2 genotypes, and treatment observations in Yao syndrome: a retrospective case series - Williamson, Katrina A.; Samec, Matthew J.; Patel, Jenny A.; Orandi, Amir B.; Wang, Benjamin; Crowson, Cynthia S.; Loftus, Edward V.; Alavi, Afsaneh; Moyer, Ann M.; Davis, John M. (Frontiers in Immunology, 2024)
Objective The aim of this study was to characterize the phenotype and genotype of patients with Yao syndrome (YAOS), with focus on comparing to prior cohorts, identifying novel features, and describing treatment observations. Methods A retrospective medical records review of patients with YAOS seen at Mayo Clinic was conducted to characterize clinical features, NOD2 genotypes, and therapeutic trials and responses. Results Twenty-two patients diagnosed with YAOS were included. Eighteen patients (81.8%) were female and twenty (90.9%) were White. Mean age at symptom onset was 24.0 ± 14.8 years. Common clinical manifestations included fever (81.8% of patients), rash (95.5%), chronic gastrointestinal symptoms (100%), arthralgia/arthritis (95.5%), and sicca symptoms (68.2%). NOD2 genotypes as single variants included IVS8 + 158 in 14 patients (63.6%), R702W in 8 patients (36.4%), 1007fs in 4 (18.2%), and one patient had only a previously unreported rare variant. Eight patients (36.4%) had compound (two or more) NOD2 variants. Potential comorbidities of YAOS observed in this cohort included gastrointestinal dysmotility, autonomic dysfunction, and mast cell activation-like symptoms. Glucocorticoid responsiveness was observed in 15 of 20 patients exposed (75%). Eleven patients (50.0%) received IL-1 inhibitor therapy, and one patient (4.5%) received IL-6 inhibitor therapy with adequate disease control. Conclusion Our findings substantiate the occurrence of fevers, arthralgia/arthritis, rash, chronic gastrointestinal symptoms, and sicca-like symptoms described previously in patients with YAOS. Novel clinical features and one NOD2 variant not previously described were identified. Glucocorticoids, biologic IL-1 inhibitors, and IL-6 receptor inhibitors appeared to be effective for treatment of patients with YAOS.